Usage of mother liquor recycling for the obtaining of Fe(VI) compounds - Golovko, Dmitriy; Golovko, Igor; Goncharova, Irina; Shevchenko, Ludmila (Eastern-European Journal of Enterprise Technologies, 2017)
In order to improve the indexes of ferrates(VI) synthesis and reduce production costs of the target product, we studied the recycling features of spent mother liquor. It is shown that the composition of mother liquors depends on the method of obtaining Fe(VI) compounds. Low-temperature salting-out is offered as the main technological decision for recycling. The solubility of K2FeO4 and some ballast salts (KCl, KNO3, K2SO4), which accumulate during the synthesis of ferrate in the mother liquor and when OH− ions are in large excess has been studied. It is shown that the solubility of the target product decreases with increasing concentration of potassium hydroxide and is 0.7 g/l in 14.3 M KOH at 20 ºС. The influence of temperature and concentration of potassium hydroxide on the solubility of ballast salts has been studied and it is found out that for the effective removal of impurities it is necessary to maintain temperature within the range 0–10 ºС at C (KOH)=14 M. It has been established that the electrochemical synthesis of crystalline K2FeO4 based on the transpassive dissolution of Fe in the concentrated NaOH solution is impractical, as profitable recycling of the spent mother liquor is practically impossible. It has been determined that with the hypochlorite method of obtaining ferrates(VI), the least amount of impurities enters the system when FeO(OH) is used as the initial Fe-containing precursor. At the same time, the least amount of ОН− anions is also used for the formation of 1 mole of the target product. Therefore, the recycling of the mother liquor for synthesis based on FeO(OH) is the simplest and the most profitable.